2019
DOI: 10.4103/sajc.sajc_76_18
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of nimotuzumab with concurrent chemoradiotherapy in unresectable locally advanced squamous cell carcinoma of head and neck: An Indian rural hospital experience

Abstract: Context:Nimotuzumab is the only anti-epidermal growth factor receptor monoclonal antibody which can be safely added to concurrent chemoradiotherapy (CRT) to improve efficacy in the management of unresectable, locally advanced squamous cell carcinoma of head and neck (LA-SCCHN). However, the evidence available on this is limited.Aims:We retrospectively investigated efficacy and safety of nimotuzumab when combined with chemoradiation for LA-SCCHN.Settings and Design:Hospital records of 39 patients from January 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…Median PFS increased by 2 months (p = 0.009) without any significant increase in toxicity ( 36 ). Other studies of nimotuzumab in SCCHN ( 37 , 38 ) also showed similar results. It can be seen that the treatment of nimotuzumab combined with chemotherapy or RT or CRT for SCCHN can improve the short-term and long-term efficacy without increasing the toxic reaction.…”
Section: Discussionsupporting
confidence: 70%
“…Median PFS increased by 2 months (p = 0.009) without any significant increase in toxicity ( 36 ). Other studies of nimotuzumab in SCCHN ( 37 , 38 ) also showed similar results. It can be seen that the treatment of nimotuzumab combined with chemotherapy or RT or CRT for SCCHN can improve the short-term and long-term efficacy without increasing the toxic reaction.…”
Section: Discussionsupporting
confidence: 70%
“…Docetaxel is recommended as a first-line therapy for recurrent, unresectable or metastatic SCCHN as a single agent or in combination with cisplatin/carboplatin with/without 5-FU/cetuximab ( 6 ). In this setting, docetaxel-based chemotherapy has reported an ORR of 33–97% in the treatment of SCCHN ( 37 , 38 ). Patients receiving NDLS-based palliative chemotherapy demonstrated an ORR of 50% and a median OS of 4.6 months (follow-up duration, 1.8–14.3 months) in the present study.…”
Section: Discussionmentioning
confidence: 99%